2006
DOI: 10.1038/sj.npp.1301196
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Vesicular Monoamine Transporter 1 Gene (VMAT1/SLC18A1) are Associated with Bipolar I Disorder

Abstract: The vesicular monoamine transporter 1 gene (VMAT1/SLC18A1) maps to the shared bipolar disorder (BPD)/schizophrenia (SZ) susceptibility locus on chromosome 8p21. Vesicular monoamine transporters are involved in transport of monoamine neurotransmitters which have been postulated to play a relevant role in the etiology of BPD and/or SZ. Variations in the VMAT1 gene might affect transporter function and/or expression and might be involved in the etiology of BPD and/or SZ. Genotypes of 585 patients with BPD type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 72 publications
2
60
1
Order By: Relevance
“…This was substantiated by Basselin et al (2006), who demonstrated that lithium reduced D 2 -like-receptor-initiated signaling in a number of brain regions, including the substantia nigra. Additionally, genetic expression studies have linked the vesicular monoamine transporter gene, which is associated with BD, to the substantia nigra, where it is expressed at higher levels than any other brain region (Lohoff et al, 2006). Thus our results suggest a link between brain structural and dopaminergic changes associated with mania.…”
Section: Brain Structural Changes Associated With the Diagnosis Of Bdmentioning
confidence: 48%
“…This was substantiated by Basselin et al (2006), who demonstrated that lithium reduced D 2 -like-receptor-initiated signaling in a number of brain regions, including the substantia nigra. Additionally, genetic expression studies have linked the vesicular monoamine transporter gene, which is associated with BD, to the substantia nigra, where it is expressed at higher levels than any other brain region (Lohoff et al, 2006). Thus our results suggest a link between brain structural and dopaminergic changes associated with mania.…”
Section: Brain Structural Changes Associated With the Diagnosis Of Bdmentioning
confidence: 48%
“…For rs 2270641, T allele was observed as the minor allele with an allele frequency of 0.480 in Emirati population whilst this allele was found to be major allele in all the Hapmap population (Table 2). However, Lohoff et al (2006) reported T allele as the minor allele with a frequency of 0.35 in a European population but significantly different from Emirati population. For rs2270637, minor G allele frequency in Emirati population was not significantly different from that of the other populations on the HapMap data.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the VMAT1 gene might affect transporter function and might be involved in the etiology of neuropsychiatric disorders. Previously, the three nonsynonymous SNPs [Thr4Pro (rs2270641), Thr98Ser (rs2270637),Thr136Ile (rs1390938)] were reported to be associated with psychiatric disorders (Lohoff et al, 2008a, b;Bly, 2005;Richards et al, 2006;Chen et al, 2007) The amino acid variant Thr136Ile in the VMAT1 gene was found associated with bipolar disorder in a case control association study conducted by Lohoff et al (2006). The Thr4Pro polymorphism was associated with SZ in Europeans (Bly, 2005) and Chinese (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family and twin studies show bipolar disorder has a strong heritable component (Lohoff et al, 2006). In bipolar disorder I, there is mania and major depression in ratio of 1: 3.…”
Section: Bipolar Disordermentioning
confidence: 99%